1995
DOI: 10.1097/00019052-199510000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin-glycoprotein complex

Abstract: SummaryDystrophin, the high molecular weight protein product of the Duchenne muscular dystrophy (DMD) gene, is localized to the sarcolemma of normal skeletal muscle but is absent from the skeletal muscle of patients with DMD and mdx mice. The predicted amino acid sequence of dystrophin suggests that dystrophin is involved in the anchoring of sarcolemmal proteins to the underlying cytoskeleton. However, the sarcolemmal proteins which are associated with or bound to dystrophin are not known and the status of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(12 citation statements)
references
References 48 publications
0
10
1
1
Order By: Relevance
“…Duchenne and Becker muscular dystrophies are X-linked disorders caused by mutation or deletion of dystrophin (51). We have found that deletion of dystrophin in the mdx mouse causes a shift in Ca 2ϩ channel voltage dependence toward more positive potentials and reduces channel potentiation.…”
Section: Effects Of Pka On Voltage Dependence Of Ca 2؉ Channel Activimentioning
confidence: 95%
“…Duchenne and Becker muscular dystrophies are X-linked disorders caused by mutation or deletion of dystrophin (51). We have found that deletion of dystrophin in the mdx mouse causes a shift in Ca 2ϩ channel voltage dependence toward more positive potentials and reduces channel potentiation.…”
Section: Effects Of Pka On Voltage Dependence Of Ca 2؉ Channel Activimentioning
confidence: 95%
“…1 is critical to the stability of muscle fiber membranes (1,2). Components of the DGC include several cytoplasmic proteins (for example dystrophin and the syntrophins) and two subcomplexes (3) of transmembrane glycoproteins, the dystroglycans (␣ and ␤; Ref.…”
Section: A Group Of Proteins Called the Dystrophin-glycoprotein Complmentioning
confidence: 99%
“…Duchenne muscular dystrophy (DMD) is a severe degenerative muscle disease caused by a mutation in the dystrophin gene, located on chromosome Xp21. Dystrophin is associated with a complex of transmembrane glycoproteins, the dystrophin‐glycoprotein complex, and acts as a transsarcolemmal linker between the subsarcolemmal cytoskeleton and the extracellular matrix [1–4]. Loss of this complex results in mechanical instability of the sarcolemma [5], rendering dystrophic muscle more susceptible to stress [6, 7]resulting in an increased activity of ‘leak' [8, 9], and/or stretch‐inactivated Ca 2+ channels [10–13].…”
Section: Introductionmentioning
confidence: 99%